Feminitives 2020 - Z. I. Mineeva (Шаги, 2022)
The paper deals with feminitives that have appeared in Russian over the past two years. During the COVID-19 pandemic there is a rapid growth of derivational activity, new person nouns appear, and feminitives are studied on a piecemeal basis. In our work we use dictionaries of neologisms from 2021, media and Internet resources. The purpose is to determine the way of word-formation, the derivational models and the meaning of the new feminitives; semantic, word-formation and structural-semantic methods are used. As a result, we identified 15 models, according to which neofeminitives were formed on the basis of personal masculine and feminine nouns, as well as on the base of concrete, abstract and other nouns. We conclude that affixation and addition are the most active and productive in derivation of Russian feminitives. The study made it possible to determine the semantic features of the new feminitives, which, like masculine agentives, designate a person on the basis of professional and non-professional activities, in relation to various aspects of life during a pandemic. The corpus of new nominations for a person consists of asymmetric parts. Quantitative asymmetry is manifested in the fact that in the “Russian Dictionary of the Coronavirus Epoch” (2021) nominations of the feminine gender (feminitives) make up 11% of all nominations of a person. Semantic asymmetry is manifested in the fact that feminitives predominantly denote women, while masculine agentives, as a rule, name a person regardless of gender, according to belonging to a group of people, which is manifested in the use of plural forms.